EiMM'10 - Proceedings of the 2nd ACM International Workshop on Events in Multimedia, Co-located with ACM Multimedia 2010: Foreword - Scherp, A. (2013)
EiMM'10 - Proceedings of the 2nd ACM International Workshop on Events in Multimedia, Co-located with ACM Multimedia 2010